2020
DOI: 10.37394/23208.2020.17.12
|View full text |Cite
|
Sign up to set email alerts
|

Medicine detection with Low Frequency Electromagnetic Signals

Abstract: This paper presents a new, non-invasive method to detect molecular structures inside materials . There have been different methods to detect molecular structures such as Chromatography, Spectroscopy and Nuclear Magnet Resonance. A brief description of these methods is presented and how they are used. Then the new method is presented using an apparatus emitting low frequency electromagnetic signals. This paper presents how the frequencies are found, that are used to detect molecular structures. The method was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…All physiology and biomedicine have now approached a certain threshold, after which the sensitivity of calculation methods should be increased and new methods for assessing changes in the parameters of not only CVS, but also other life support systems (including brain neural networks) should be created [10][11][12]. Within the framework of the new theory of chaos-self-organization (TCS), we have now shown the lack of statistical stability of samples of various parameters of the functions of the human body [1][2][3][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. This is now referred to as the Eskov-Zinchenko effect (EES) [1-3, 5, 6, 13-16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All physiology and biomedicine have now approached a certain threshold, after which the sensitivity of calculation methods should be increased and new methods for assessing changes in the parameters of not only CVS, but also other life support systems (including brain neural networks) should be created [10][11][12]. Within the framework of the new theory of chaos-self-organization (TCS), we have now shown the lack of statistical stability of samples of various parameters of the functions of the human body [1][2][3][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. This is now referred to as the Eskov-Zinchenko effect (EES) [1-3, 5, 6, 13-16].…”
Section: Resultsmentioning
confidence: 99%
“…HE influence of industrial electromagnetic fields (EMF) of low frequency and low intensity on the human body is a poorly studied problem of human biophysics and ecology. The study of this problem is especially relevant for workers in the oil and gas sector in the Far North [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is observed that it takes a certain charging time until the sensor starts responding to the material and detecting it. After this initial charging time is achieved, a maximum inertia feedback response is observed in the motion of the sensor slowing it down [23][24][25]. It should be noted that it is a non-destructive and non-invasive method, which means that when we use a material, no changes happen to its composition, and it is not tampered with or altered by any means.…”
Section: Introductionmentioning
confidence: 99%